UMP Students represent Asia-Pacific in the Falling Wall Labs Competition in Berlin Germany - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 21 October – Winning the Asia-Pacific 3 Minute Thesis Competition is not an end for Ashwin Charles Benedict. Currently pursuing his doctorate studies at Faculty of Chemical & Natural Resources Engineering (FKKSA), he is now preparing himself to be competing in Falling Wall Labs 2017 in Berlin, Germany on 8 and 9 November 2017 with his research entitled Catalyzing Change: Light at the end of the Tunnel.